PENERAPAN KONSEP “5S” DALAM UPAYA MENCIPTAKAN LINGKUNGAN KERJA YANG ERGONOMIS DI STIA LAN BANDUNG - Teni Listiani (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
An organization could increase its employee’s productivities through various approaches. One of them is through the ergonomic approach. In this approach, it is important to harmonize the employees with their working environment so that it may create security and working satisfaction. As a result, it will contribute to increasing productivity. Security and satisfaction in the work place can be achieved through the implementation of 5S concept (Seiri, Seiton, Seiso, Seiketsu and Shitsuke). It is a simple concept. However, putting it into practice needs awareness, discipline and high commitment from every employee.